A Comparative Study on Dual-phase Enhanced CT, CT Perfusion and Histopathology in Edges of Hepatocellular Carcinoma - Rongjie Bai; Jinping Li; Shaohua Ren; HuiJie Jiang; Xinding Liu; Zaisheng Ling (International Journal of Medical Research, 2014)
Background: The morphological characteristics of HCC edge not only predict the biological behavior of the tumor, but also determine the treatment. Method: 47 cases of HCC borders were divided into three morphological types based on enhanced CT findings. Clear edges (Type I): The tumor boundary was clearly displayed at dual-phase CT. Blurry edges (Type II): The boundary between tumor and normal liver tissues was blurry at dual-phase CT. Mixed type (Type III): Part of tumor edge was clear or had an incomplete capsule formation, another part of tumor edge had a blurry boundary with normal liver tissues, and the above two types of performance were seen at dual-phase CT. All patients underwent CT perfusion (CTP) imaging. The correlations between microvessel density (MVD) and the CTP parameters were analyzed. Results: In 47 cases of HCC, the MVD in edge areas of type II was higher than that in type I, and the difference was statistically significant (P <0.05).The MVD in clear edge areas of type III was lower than that in Blurry edges (P <0.01). Positive linear correlations existed between the values of HAP, HAF, and HBF versus MVD (P < 0.05). HPP showed a negative correlation with MVD measurements (P < 0.05). Conclusion: The CT classification of the tumor edges can roughly evaluate the characteristics of the tumors at the macro level, and the CTP imaging in tumor edges can acquire more information at the micro level and reflect the tumor characteristics more specifically and comprehensively.